1999
DOI: 10.1097/00005344-199906000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Role of A2A Receptor in the Modulation of Myocardial Reperfusion Damage

Abstract: Adenosine protects myocardium from ischemia and reperfusion damage; however, the mechanism of action is still under discussion. We investigated whether (a) adenosine protects isolated crystalloid-perfused rabbit heart from ischemia/ reperfusion injury; (b) this action is receptor mediated and what receptor subtypes are involved, and (c) this action is dependent on an enhanced nitric oxide production. Our results showed a cardioprotective effect of adenosine (10(-4) M), of nonselective adenosine-receptor agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…2,23 Similar cardioprotective effects also have been reported in exsanguinous isolated heart models. [11][12][13] Hence, the attenuation of postischemic myocardial injury by A 2A AR agonists has been attributed to their actions on the vasculature (or myocytes) under certain conditions. 13,24 Several other studies using isolated heart models revealed that A 2A AR activation does not alter ventricular myocyte cAMP levels and exerts no protective effect against myocardial ischemia-reperfusion injury, 14,15,21 suggesting that A 2A ARs either were expressed at low levels or were not functionally significant in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,23 Similar cardioprotective effects also have been reported in exsanguinous isolated heart models. [11][12][13] Hence, the attenuation of postischemic myocardial injury by A 2A AR agonists has been attributed to their actions on the vasculature (or myocytes) under certain conditions. 13,24 Several other studies using isolated heart models revealed that A 2A AR activation does not alter ventricular myocyte cAMP levels and exerts no protective effect against myocardial ischemia-reperfusion injury, 14,15,21 suggesting that A 2A ARs either were expressed at low levels or were not functionally significant in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,11 The salutary effect of A 2A AR activation against myocardial ischemia-reperfusion injury has been reported in intact animal models 2,3 and in several ex vivo experiments. [11][12][13] However, other ex vivo studies showed that activation of A 2A ARs exerts no protective effects to the myocardium during postischemic reperfusion. 14,15 The conflicting findings in these experiments may be attributed to an important role for blood-borne leukocytes that are absent in exsanguinous hearts and/or variations in A 2A AR distribution or function in different animal species.…”
mentioning
confidence: 99%
“…Recently, 0008 Yang et al demonstrated that the protective effect of NECA, an agonist of adenosine, on reperfusion injury was abolished by l-NAME in intact rabbit hearts, suggesting a possible involvement of NO in the action of NECA [5]. Nonetheless, there has also been evidence that NO is not responsible for adenosine-induced early preconditioning [6] or adenosineinduced protective effect on reperfusion injury [7]. Although the reason for this discrepancy is not clear, the role of NO was determined by either suppressing NOS activity or detecting NOS expression, without direct evidence of whether adenosine verily altered intracellular NO concentration in cardiomyocytes or not.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there have also been reports showing both anti-inflammatory (8,26) and anti-infarct (1) effects of A 3 adenosine receptor activation. Nevertheless, the cardioprotective effects of adenosine during reperfusion injury appear to be mediated at least in part by A 2A receptor activation (2,13,15,18). Activation of A 2A receptors results in increased intracellular adenosine 3Ј,5Ј-cyclic monophosphate (cAMP) concentration, resulting in activation of protein kinase A and inhibition of multiple steps in the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%